2006
DOI: 10.1088/0953-8984/19/2/026219
|View full text |Cite
|
Sign up to set email alerts
|

Metastable phase formation in the immiscible Cu–Co system studied by thermodynamic, molecular dynamics andab initiocalculations together with ion beam mixing

Abstract: For the equilibrium immiscible Cu-Co system with a positive heat of formation of +10 kJ mol −1 , ab initio calculations were used to predict the physical properties of the metastable D0 19 and L1 2 structures for the Cu 75 Co 25 phases and the D0 19 structure for the Cu 25 Co 75 alloy. Based on the ab initio calculation results, an n-body Cu-Co potential was constructed and proven to be realistic. Applying the constructed Cu-Co potential, molecular dynamics simulations predict that the amorphous phase could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 37 publications
2
10
0
2
Order By: Relevance
“…It is well-known that Cu-Co is equilibrium immiscible system with positive heat of formation of +10 kJ/mol and therefore does not form any stable intermetallic compounds [1]. However, when thin layers of Cu and Co are staked together in the form of thin film multilayers, their interfacial alloys may be formed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-known that Cu-Co is equilibrium immiscible system with positive heat of formation of +10 kJ/mol and therefore does not form any stable intermetallic compounds [1]. However, when thin layers of Cu and Co are staked together in the form of thin film multilayers, their interfacial alloys may be formed.…”
Section: Introductionmentioning
confidence: 99%
“…This happens due to a large difference between the surface free energy ( ) of Cu and Co. It is reported in the literature that metastable structure of a mixed CuCo phase may exist at the interfacial regions in Cu/Co thin film multilayers [1][2][3]. In case of Cu/Co multilayers, growth of Co-on-Cu is thermodynamically unfavorable because Co > Cu [4].…”
Section: Introductionmentioning
confidence: 99%
“…Ion beam mixing is far from being an equilibrium process and thus it can overcome the problem above. Really, IBM is frequently applied to produce various nonequilibrium phases like amorphous alloys with negative or positive heat of mixing [1][2][3][4][5][6][7][8][9]. To explain these phenomena it is frequently argued that the fast quenching is responsible for the process.…”
Section: Formation Of Ni 3 Cmentioning
confidence: 99%
“…There are, however, explanations that are more refined. It was observed that multilayer systems of immiscible elements could be converted by IBM to amorphous nonequilibrium alloys [6,7]. In these cases the total energy of the system decreases despite of the positive heat of formation of the alloy, since the mixing removes the high energy interfaces.…”
Section: Formation Of Ni 3 Cmentioning
confidence: 99%
See 1 more Smart Citation